There are these days, so many newspaper articles about him, or someone like him - Alys, Hannah (My University, 2017)
Each year MacEwan University chooses a work of contemporary Canadian fiction. The Book of the Year is explored through classes, author readings, workshops, and contests. This piece belongs to the Book of the Year Poster Series project where Design Studies students interpreted it through type and image. The exhibited work showed excerpts from Love Enough by Dionne Brand. Course: DESN330 Typography II. Instructor: Constanza Pacher.
Exhibited March 9 - 21, 2018 at Allard Hall, MacEwan University.
Keywords: typography; poster design; Love Enough; Dionne Brand; MacEwan Book of the Year